-8y+3y-(10)+2y=11

Simple and best practice solution for -8y+3y-(10)+2y=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8y+3y-(10)+2y=11 equation:


Simplifying
-8y + 3y + -1(10) + 2y = 11

Multiply -1 * 10
-8y + 3y + -10 + 2y = 11

Reorder the terms:
-10 + -8y + 3y + 2y = 11

Combine like terms: -8y + 3y = -5y
-10 + -5y + 2y = 11

Combine like terms: -5y + 2y = -3y
-10 + -3y = 11

Solving
-10 + -3y = 11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -3y = 11 + 10

Combine like terms: -10 + 10 = 0
0 + -3y = 11 + 10
-3y = 11 + 10

Combine like terms: 11 + 10 = 21
-3y = 21

Divide each side by '-3'.
y = -7

Simplifying
y = -7

See similar equations:

| 5+(n+9)=-3 | | 15=2t+.806t | | 25+50h=8 | | 3y^2+27y+60=0 | | 3(x+2)-10(x+10)=-7-8 | | 4t=2(7x+15) | | 6(3x+7)=3x+2-5x | | 3+5h=5 | | 10(x-2)=2(x+9) | | 34-0.5d=26 | | 2.1(a+2)=2.1a+4.2 | | 4-4(x-2)=-1+3(x-5+2) | | 3n-6-6+2n=4n-12 | | 0=-4x+21-x^2 | | 2x(5.83)=x(5.83) | | 5x=8(6x-1)-35 | | 4x^3+12x^2+2=0 | | 11-(-10)-5/6= | | 4[2-3(2x+4)]=5x | | (y-6)-(5y-7)= | | log(x)=1.9 | | y=9x^2-36 | | -40=6x+8 | | 5(1x+7)=20 | | (y-5)-(5y-7)= | | 3x+10=15x-8 | | 5(-2x+8)=-50 | | 4(2+2)= | | 2x+3-5x+7=1 | | 17y^2+5y-126=0 | | 2x+3-5x+7=2 | | 8y-3y=44 |

Equations solver categories